Project-Based Learning Case Studied Model to Improving Learner Skills on Industry Revolution 4.0 - Iskandar; Raimon Efendi; Ricky Ramadhan Harahap; Irwan Yusti (Universitas Pendidikan Ganesha, 2022)
There is a gap in visual programming Learning that could be more optimal and has been unable to improve 4th- century competencies. This study aims to develop a visual programming Learning model in vocational education that can improve students' Learning abilities. This type of research is Research and Development, which refers to the ADDIE model. The subjects involved in the limited trial of the PJBL-CS model were 15 lecturers and 25 students. The trial subjects were expanded to include 110 respondents in the fourth semester of the graphic design program. Data collection will be carried out using a questionnaire. The analysis technique used the Aiken'V test, and the validity used the expert test and Focus Group Discussion (FGD). The normality test of the data distribution was carried out using Kolrnogorov Srnirnov statistics. According to experts, the result of the study is models, and support systems meet the validity standards, are based on research and development models, and are acceptable for implementation. The model that is made reliable, gets an average of 86.67 points from lecturers and 86.00 points from students. Research has produced a Case Study Project-Based Learning Model that provides opportunities for students to think critically and creatively, collaborate, and communicate well, which can learn anytime, anywhere, forming students to study independently and creating connected Learning between students and lecturers.